2022
DOI: 10.1097/pg9.0000000000000231
|View full text |Cite
|
Sign up to set email alerts
|

Follicular Dendritic Cell Sarcoma in a Patient With Adolescent-Onset Crohn’s Disease Exposed to Multiple Immunomodulator and Biologic Therapies

Abstract: Children and adolescents with inflammatory bowel disease are often treated with immunomodulators (thiopurines, methotrexate) and biologics (anti-TNF, anti-integrin) for extended periods despite concerns about long-term safety. Here, we report a case of follicular dendritic cell sarcoma, a very rare malignancy, and the first reported presentation in a patient with inflammatory bowel disease exposed to infliximab, methotrexate, and vedolizumab. We review the key clinical features and diagnostic factors of this m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…For instance, our dataset included a patient receiving an anti-TNF who was hospitalized for a new diagnosis of sarcoma. Sarcomas have previously been reported in the context of children with IBD using anti-TNFs, 24 although multiple long-term observational studies have not consistently found a link between anti-TNF use and an increased risk of cancer in adults. 25,26 Non-steroid medications for IBD are not uniformly effective.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, our dataset included a patient receiving an anti-TNF who was hospitalized for a new diagnosis of sarcoma. Sarcomas have previously been reported in the context of children with IBD using anti-TNFs, 24 although multiple long-term observational studies have not consistently found a link between anti-TNF use and an increased risk of cancer in adults. 25,26 Non-steroid medications for IBD are not uniformly effective.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, our dataset included a patient receiving an anti-TNF who was hospitalized for a new diagnosis of sarcoma. Sarcomas have previously been reported in the context of children with IBD using anti-TNFs 24 , although multiple long-term observational studies have not consistently found a link between anti-TNF use and an increased risk of cancer in adults 25,26 . Future directions of this work include external validation using data from additional centers, expansion to additional disease states outside of IBD, and downstream studies designed to identify new drug-SAEs associations more rigorously using aggregated data.…”
Section: Discussionmentioning
confidence: 99%